Bibliometric analysis of the publications of Geophysical Institute of Peru: production, collaboration, impact and scientific leadership - Lopez-Ramirez, Joselyn (2025)
Bibliometrics, a key discipline within information sciences, allows to diagnose and evaluate the results of scientific research. In this context, the present study analyzes the scientific production of the Instituto Geofísico del Perú (IGP) indexed in Scopus during the period 1961-2021. Output, collaboration, impact and leadership indicators were used, in addition to evaluating the fit of Lotka's Law to the data through the generalized inverse power model. The analysis reveals that the IGP has published 624 documents, evidencing an increasing pattern in its production volume. The percentage of international collaboration predominates (82.7%), as well as publications in quartile 1 journals (71.9%) and the percentage of documents without institutional leadership (67%). Using the generalized inverse power model, it is verified that Lotka's law does not fit the data of the IGP's scientific literature. By integrating various bibliometric indicators, this study constitutes a strategic tool for research management, offering valuable input for decision-making. Finally, recommendations for researchers, managers and decision-makers are presented, as well as proposals for future lines of research aimed at institutional strengthening.